2011
DOI: 10.1519/jpt.0b013e31820aa829
|View full text |Cite
|
Sign up to set email alerts
|

Fall Risk Assessment Among Older Adults With Mild Alzheimer Disease

Abstract: While the PPT 7-item was able to detect differences in mobility between subjects with history of falls and subjects without history of falls in subjects with mild AD, total PPT 7-item score did not predict falling. Gait aid usage was more strongly related to falling in these subjects. Early detection of fall risk in individuals with mild AD is important to prevent injuries and moderate costs of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…This was followed by a group of neurological diseases with an almost four times higher likelihood (55–60%) of falls, consisting of dementia, epilepsy, other movement disorders, other vascular diseases and peripheral neuropathy. These diseases are also known to carry a high risk for falls, with an annual fall rate of 60–80%12 40 in patients with Alzheimer's disease and 55–65%41–43 in patients with peripheral neuropathy. The only study conducted on falls in elderly patients suffering from epilepsy is one on care facility residents, providing a 5-year fall incidence of 83% 44.…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by a group of neurological diseases with an almost four times higher likelihood (55–60%) of falls, consisting of dementia, epilepsy, other movement disorders, other vascular diseases and peripheral neuropathy. These diseases are also known to carry a high risk for falls, with an annual fall rate of 60–80%12 40 in patients with Alzheimer's disease and 55–65%41–43 in patients with peripheral neuropathy. The only study conducted on falls in elderly patients suffering from epilepsy is one on care facility residents, providing a 5-year fall incidence of 83% 44.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies explored the risk of falling in individuals with MCI and early-stage dementia. Ryan, McCloy, Rundquist, Srinivasan, and Laird (2011) found poor scores on the Physical Performance Test and use of a gait aid associated with a history of falls in individuals with mild Alzheimer's disease (N = 43). Gleason, Gangnon, Fischer, and Mahoney (2009) conducted a secondary analysis of falls in older adults from the control group of a RCT (N = 172), and reported increased falls over 1 year associated with each decrement in MMSE scores ranging from 22 to 29.…”
Section: Increased Risk Of Fallingmentioning
confidence: 97%
“… 2 Together, these things can worsen preexisting conditions, complications, injuries, and social withdrawal, as well as generally decrease quality of life among older adults. 2 3 4 5 The most common cause for injuries among older adults is falls. In the United States, it is estimated that 30% of the older adult population aged 65 years and older are injured due to falling each year.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, it is estimated that 30% of the older adult population aged 65 years and older are injured due to falling each year. 3 A fall is defined as an unintentional change of body posture in unexpected situations, which causes individuals to trip or lay down on either the floor or somewhere of lower altitude than the current body position. 4 Falls can cause both mental and physical suffering, and it is reported that even individuals who experienced falls without any physical injury might have a fear of falling, which can limit their physical activities and eventually lead them to reside in long-term care facilities and institutions for older adults.…”
Section: Introductionmentioning
confidence: 99%